2015
DOI: 10.1128/iai.02427-14
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Response Specific to the Capsular Polysaccharide Is Impaired in Streptococcus suis Serotype 2-Infected Animals

Abstract: bStreptococcus suis serotype 2 is an extracellular encapsulated bacterium that causes severe septicemia and meningitis in swine and humans. Albeit crucial in the fight against encapsulated bacteria, the nature of the capsular polysaccharide (CPS)-specific antibody (Ab) response during S. suis type 2 infection is unknown. We compared for the first time the features of CPS-specific versus protein-specific Ab responses during experimental infections with live virulent S. suis type 2 in mice. The primary protein-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 73 publications
5
40
0
Order By: Relevance
“…In contrast, S. suis serotype 2 CPS alone is unable to induce any significant antibody response, even when adjuvanted with TiterMax Gold or Stimune or when combined with the TLR ligand CpG in mice (unpublished results). Furthermore, previous studies using live S. suis serotype 2 infection showed modest IgM and no isotype-switched IgG anti-CPS antibody titers in pigs and in mice even after an experimental reinfection (17). Thus, S. suis serotype 2 CPS seems to be particularly nonimmunogenic, making it an ideal candidate for evaluation of the effect of glycoconjugation on immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, S. suis serotype 2 CPS alone is unable to induce any significant antibody response, even when adjuvanted with TiterMax Gold or Stimune or when combined with the TLR ligand CpG in mice (unpublished results). Furthermore, previous studies using live S. suis serotype 2 infection showed modest IgM and no isotype-switched IgG anti-CPS antibody titers in pigs and in mice even after an experimental reinfection (17). Thus, S. suis serotype 2 CPS seems to be particularly nonimmunogenic, making it an ideal candidate for evaluation of the effect of glycoconjugation on immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…All experiments involving mice were conducted in accordance with the guidelines and policies of the Canadian Council on Animal Care and the principles set forth in the Guide for the Care and Use of Laboratory Animals by the Animal Welfare Committee of the University of Montreal. Five-to 6-week-old C57BL/6 female mice (Charles River, Wilmington, MA), largely used for studies on S. suis pathogenesis (17,(33)(34)(35), were immunized subcutaneously with different doses of the S. suis CPS conjugate preparations (see Results) in 0.1 ml PBS on day 0 and boosted on day 21. In a first set of experiments aimed to compare different adjuvants, 3 groups (n ϭ 10) received 25 g of the 2:1 mixed conjugate dissolved in PBS adjuvanted with either 20 g of CpG oligodeoxyribonucleotide (ODN) 1826 (InvivoGen, San Diego, CA), Stimune (Prionics, La Vista, NE), or TiterMax Gold (CytRx Corporation, Norcross, GA) following the manufacturers' recommendations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CPS is a poor immunogen due to its thymus-independent property and cannot induce sufficient immune response [8]. Study showed that coupling S. suis type 2 CPS to tetanus toxoid can induce T cell-dependent response, inducing IgM and IgGs for protection against challenges in mice and pigs [9, 10]. In addition, immunization with certain virulence factors, such as suilysin, muramidase-released protein (MRP) and extracellular factor (EF), has been demonstrated to protect pigs from challenge with homologous or heterologous strains of S. suis .…”
Section: Introductionmentioning
confidence: 99%
“…As isotype-switched IgG plays an important role in the fight against encapsulated extracellular bacteria (35, 36), antibodies (Abs) to the entire encapsulated SC19 strain were assessed after 2015033 immunization. Immunized mice exhibited a significant increase in IgG, IgG1, and IgG2a, which remained at high levels until the end of the experiment, while mice injected with phosphate buffered saline (PBS) showed no detectable increases (Fig.…”
Section: Resultsmentioning
confidence: 99%